The relationship between physical abilities, ball-carrying and tackling among elite youth rugby league players - Waldron, M.; Worsfold, P. R.; Twist, C.; Lamb, K. (Journal of Sports Sciences, 2014)
This study investigated the relationship between the physical abilities of adolescent rugby league players and tackling and ball-carrying skills performed during matches, across three seasons (under-15 to under-17). The players were measured each season for acceleration (10-30 m), peak and mean speed (10-30 m), sprinting force (10-30 m), aerobic power, counter-movement jump (CMJ) height and jumping power. The matches were filmed and analysed for ball-carrying and tackling frequency per minute (successful and unsuccessful outcomes). There were strong relationships between successful carries/min and 10 m force in the under-15 (R = 0.61, P < 0.001), under-16 (R = 0.69, P < 0.001) and under-17 groups (R = 0.64, P < 0.001). There were also strong and moderate relationships between predicted vertical power and successful carries/min in the under-15 (R = 0.63, P = 0.011) and under-17 group (R = 0.40, P = 0.030), respectively. There were no relationships between carries or tackles and any other performance indicators. These findings suggest that acceleration, in accordance with gains in body mass, support ball-carrying but not tackling performance. Performance measurements, such as CMJ or aerobic power, do not support ball-carrying ability among youth rugby league players.